Horror Studies between Humanistic Interdisciplinarity and Scientific Consilience: A Conversation with Darryl Jones and Mathias Clasen. (31st December 2018) - Ambasciano, Leonardo; Clasen, Mathias; Jones, Darryl
Abstract : The present thought-provoking conversation engages two accomplished scholars of horror, Darryl Jones and Mathias Clasen, on the multimedia history of horror through their disciplinary viewpoints, respectively, literary studies and the cognitive sciences. Following the publication of their most recent books on the topic (Jones 2018; Clasen 2017), the main theme discussed herein is the possibility of creating an interdisciplinary bridge, and, possibly, developing a cross-disciplinary integration between different scholarly strategies. Other themes considered include: consilience and coexistence between humanistic and scientific approaches; potential intradisciplinary issues around the establishment of an interdisciplinary dialogue; the differential heuristic gains of qualitative analyses through different disciplinary toolboxes; the existence of a bewildering historical array of theories explaining the appeal of horror as a genre and a collection of tropes; the thematic interconnection between horror and religion. The conversation also includes a series of artistic and scholarly suggestions to further explore the topics debated.